FORMULATION AND IN-VITRO EVALUATION OF BILAYER TABLET CONTAININGZOLMITRIPTAN AND NAPROXEN (CAHIERS MAGELLANES-NS, 2024)
Migraine is a chronic neurological disorder and characterized by splitting headaches. A combination of Zolmitriptan (ZT) and Naproxen sodium (NS) was found to be effective. Time to reach Cmax and biological half lives of both the drugs are different and hence optimum levels of both the drugs cannot be maintained simultaneously in the blood when these drugs are administered orally in the form of conventional tablets. Therefore the objective of present investigation was formulation development and in vitro evaluation of a bi layer tablet dosage form containing ZT and NS in a fixed dose combination as immediate release layer and a delayed release layer containing ZT to maintain optimum plasma levels of both drugs at a time and for a prolonged period. Formulation variables for immediate release layer include Crospovidone, Croscarmellose sodium and Sodium starch glycolate as super disintegrants. Carboxy Methyl Ethyl cellulose was used as delayed release polymer. Each layer was optimized individually and best compositions were selected. Using direct compression method bi layer tablets were prepared and evaluated. The cumulative percent drug release versus time plots of ZT from bi layer tablets indicate the pattern of drug release. The rate of drug release followed first order kinetics. Differential Scanning Calorimetry and Fourier infrared spectroscopic studies revealed the absence of incompatibility between drugs and excipients.